PEMANFAATAN EKOSISTEM DALAM AL-QUR’AN: UPAYA MENUJU PELESTARIAN LINGKUNGAN - Dewi Syafitri Oktaviani; Apriyanti; Kamaruddin (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
The environmental crisis is so bad that it certainly causes various problems in the lives of living things, both humans, animals and plants. Excessive exploitation of natural resources without recovery can cause damage to the balance of nature. Land, water, and air become polluted which will eventually threaten life on earth. This research is shown to discuss the level of human awareness in maintaining the balance of ecosystems, both biotic and abiotic. This research will be described using thematic interpretation method. The results of this study conclude that prioritizing the existence of living things with all their functions is an important clue to the power of Allah SWT., because every living thing is created nothing in vain. Humans as creatures created by Allah SWT. with its perfection, must provide protection and preservation. Efforts to protect and utilize nature can be done by planting trees and reforestation, protecting natural resources, keeping the air clean, maintaining and utilizing water and maintaining the balance of the ecosystem.